The civic-minded instructional designers framework: an alternative approach to contemporary instructional designers’ education in higher education - Yusop, F.D.; Correia, A-P. (Blackwell Publishing, 2011)
This paper argues that an emphasis on training-for-the-job approaches has distracted designers from thinking about the meaning of their profession and the grand purpose of practising instructional design. Drawing from literature in the ﬁelds of sociology and educational technology, this paper synthesises discourses on civic professionalism in instructional design and technology, and proposes a conceptual framework that highlights the roles and qualities of a civic-minded instructional designer. It is claimed that a critical discussion on civic professionalism in the ﬁeld of educational technology can offer an alternative perspective on educating instructional designers, and have practical implications on instructional design and technology curricula in higher education.